2010
DOI: 10.1016/j.vaccine.2010.10.033
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Psn, HmuR and a modified LcrV protein delivered to mice by live attenuated Salmonella as a vaccine against bubonic and pneumonic Yersinia pestis challenge

Abstract: We evaluated the ability of Yersinia pestis antigens HmuR, Psn and modified forms of LcrV delivered by live attenuated Salmonella strains to stimulate a protective immune response against subcutaneous or intranasal challenge with Y. pestis CO92. LcrV196 is a previously described truncated protein that includes aa 131–326 of LcrV and LcrV5214 has been modified to replace five key amino acids required for interaction with the TLR2 receptor. Psn is the outer membrane receptor for the siderophore, yersiniabactin, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
42
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
5
3
1

Relationship

4
5

Authors

Journals

citations
Cited by 32 publications
(44 citation statements)
references
References 51 publications
2
42
0
Order By: Relevance
“…Furthermore, we demonstrate that genes encoding bacterial systems for iron acquisition, including the yersiniabactin system, are highly expressed during natural, uncomplicated cystitis in women. Overall, our data support the yersiniabactin system as a therapeutic target to prevent or treat UPEC-mediated UTI and reinforce the potential of the yersiniabactin system as a common target for several, increasingly multidrug-resistant, Gram-negative enteric pathogens (38,39).…”
Section: Figsupporting
confidence: 73%
“…Furthermore, we demonstrate that genes encoding bacterial systems for iron acquisition, including the yersiniabactin system, are highly expressed during natural, uncomplicated cystitis in women. Overall, our data support the yersiniabactin system as a therapeutic target to prevent or treat UPEC-mediated UTI and reinforce the potential of the yersiniabactin system as a common target for several, increasingly multidrug-resistant, Gram-negative enteric pathogens (38,39).…”
Section: Figsupporting
confidence: 73%
“…The coated plates were incubated overnight at 4°C. The procedures for measuring antibody titer were described in our previous report (65). Absorbance readings that were 0.1 higher than PBS control values were considered to represent a positive result.…”
Section: Table 2 Primers Used In This Workmentioning
confidence: 99%
“…Escherichia coli and S. Typhimurium UK-1 strains were routinely cultured at 37°C in LB broth [19] or on LB agar. S. Typhimurium UK-1 mutant strains were supplemented with 50 μg/ml of Diaminopimelic acid (DAP), 0.05% arabinose or 0.1% mannose when necessary for bacterial growth as described in our previous work [12]. Carbohydrate-free nutrient broth (NB) was used for growth when determining LPS profiles.…”
Section: Methodsmentioning
confidence: 99%
“…We found that recombinant attenuated Salmonella vaccine (RASV) strains synthesizing LcrV196 or Psn individually protected mice against subcutaneous (s.c.) or intranasal (i.n.) challenge with Y. pestis CO92 [12]. Also, immunization with a RASV delivering YadC induced partial protection in mice against bubonic plague, but not pneumonic plague [13].…”
Section: Introductionmentioning
confidence: 99%